A kind of slag-based fine aggregate, cementitious material and ultra-high performance concrete and preparation method and application thereof
By modifying the hole slag, a base fine aggregate and gelled material suitable for ultra-high performance concrete is formed, which solves the problem of poor application effect of hole slag in concrete, and achieves improvement of material performance and resource conservation, which is in line with the development trend of green building materials.
Patent Information
- Application Number
- CN202411921292.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the existing ultra-high performance concrete production, the demand for high-performance cementitious materials and aggregates increases carbon emissions and resource consumption. At the same time, as solid waste materials, the application effect of hole slag in concrete is poor, affecting the mechanical properties and durability.
Through a series of modification techniques, including grinding, calcining, nanorepairing and carbon dioxide mineralization, the cave slag is improved to form cave slag-based fine aggregate and gelling materials, used to replace cement and river sand to prepare ultra-high performance concrete.
It improves the physical and chemical properties of the hole slag, improves the performance stability of the material, enables it to replace traditional materials, significantly improves the compressive strength and durability of ultra-high performance concrete, reduces dependence on natural resources, reduces production costs, and achieves carbon capture and reduces greenhouse gas emissions.
Smart Images

Figure CN119349913B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a slag-based fine aggregate, a cementitious material and ultra-high performance concrete, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-high performance concrete (UHPC) is a building material with excellent mechanical properties and durability, and is widely used in high-demand structures such as bridges and high-rise buildings. However, the production cost of UHPC is relatively high, and the demand for high-performance cementitious materials and aggregates in particular increases carbon emissions and resource consumption.
[0004] A large amount of tunnel slag (hereinafter referred to as "tunnel slag") is generated during the excavation of underground projects such as tunnels and chambers. As an engineering waste, the stacking of tunnel slag not only occupies a large amount of land, but also causes serious pollution to the environment. Compared with natural aggregates, tunnel slag has a large number of microcracks and structural defects inside and is easy to absorb water and expand. There are also large differences in chemical properties. Therefore, its application effect as a substitute for natural aggregate in concrete (especially ultra-high performance concrete) is poor, which will affect the mechanical properties and durability of concrete and is difficult to be widely used. Therefore, the recycling of tunnel slag as a solid waste is low. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a slag-based fine aggregate, a cementitious material and an ultra-high performance concrete and a preparation method and application thereof. Through a series of modification technologies, including grinding, calcination, nano-repairing and carbon dioxide mineralization treatment, the physical and chemical properties of the slag are improved, the performance stability of the material can be improved, and it can be used to replace cement and river sand in the preparation of UHPC.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, a slag-based fine aggregate is prepared by raw materials comprising the following components in parts by weight: 100 parts of slag, 0.5-1 parts of nano-alumina, and 0.1-0.3 parts of carbon dioxide.
[0008] In a second aspect, the method for preparing the above-mentioned slag-based fine aggregate comprises the following steps:
[0009] S11, crushing the slag into a set particle size;
[0010] S12, carbonizing the crushed slag for 2-4 hours under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5 MPa;
[0011] S13, mixing and stirring the carbonized slag with nano-alumina to obtain slag-based fine aggregate.
[0012] In a third aspect, a slag-based ultra-high performance concrete comprises the following components in parts by weight: 550-650 parts of cement, 145-175 parts of fly ash, 124-146 parts of silica fume, 200-300 parts of the above-mentioned slag-based cementitious material, 400-500 parts of the above-mentioned slag-based fine aggregate, 400-500 parts of natural river sand, 60-100 parts of fiber, 4-8 parts of water reducer and 190-250 parts of water;
[0013] The slag of the slag-based cementitious material and the slag of the slag-based fine aggregate have the same source;
[0014] The raw materials for preparing the slag-based cementitious material include slag and carbon dioxide in a mass ratio of 100:(0.1-0.3).
[0015] In a fourth aspect, the method for preparing the above-mentioned slag-based ultra-high performance concrete comprises the following steps:
[0016] S31, mixing cement, fly ash, silica fume, slag-based cementitious material, slag-based fine aggregate and natural river sand to obtain a mixed material;
[0017] S32, mixing water and a water reducing agent, adding the mixture to the mixed material and stirring to obtain an ultra-high performance concrete slurry;
[0018] S33, adding fibers to the ultra-high performance concrete slurry, stirring and pouring into shape;
[0019] S34. Curing the poured ultra-high performance concrete for 24 to 48 hours under the conditions of a carbon dioxide concentration of 20 to 30% and a gas pressure difference of 0.4 to 0.5 MPa.
[0020] A fifth aspect is the application of the above-mentioned slag-based ultra-high performance concrete, which is to use the slag-based ultra-high performance concrete in the fields of bridge engineering and underground engineering.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention performs carbonization treatment and nano-repair on the slag-based fine aggregate with carbon dioxide. The carbonization process first fills the larger cracks and pores, while the nano-alumina can penetrate into the finer cracks, providing a higher level of repair effect, forming a dual repair mechanism, effectively repairing the microcracks and pores in the slag, improving its physical properties, and reducing water absorption and expansion. The treated slag fine aggregate can significantly improve the compressive strength and durability of ultra-high performance concrete, making its application effect in high-strength engineering more outstanding.
[0023] 2. The present invention activates the slag cementitious material through grinding and calcination technology, which enhances the cementitious properties of the slag and enables it to partially replace traditional cement. The calcined slag material is combined with carbon dioxide carbonization technology, which not only improves the mechanical properties of the material, but also significantly improves the compressive strength and durability of ultra-high performance concrete, ensuring its long-term use in high-demand structures.
[0024] 3. In the ultra-high performance concrete of the present invention, the tunnel slag is deeply treated through a comprehensive optimization scheme (including grinding, calcination, nano-repairing and carbon dioxide carbonization treatment, etc.), which enhances the physical and chemical properties of the slag, improves the performance stability of the material, successfully converts the waste slag into raw materials in ultra-high performance concrete, and reduces the dependence on natural aggregates and cement. In the preparation process, the carbon dioxide curing technology is carried out early after the concrete is poured, and the carbon dioxide reacts with the calcium hydroxide in the concrete to form calcium carbonate, forming a dense microstructure, which not only improves the early strength of the concrete, but also further improves its long-term durability. Not only does it alleviate the problem of waste stacking, but it also reduces the exploitation of natural resources, reduces the production cost of ultra-high performance concrete, and contributes to environmental protection and resource conservation. In addition, the carbon dioxide gas emitted by the industry is effectively utilized to improve the strength and durability of the material, while achieving carbon capture, which can effectively reduce greenhouse gas emissions and conform to the development trend of green building materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 This is a physical picture of the slag-based fine aggregate in Example 1.
[0027] Figure 2 This is a diagram showing the characterization results of the slag-based fine aggregate in Example 1.
[0028] Figure 3 This is the characterization result diagram of the slag-based fine aggregate in Comparative Example 1.
[0029] Figure 4 This is the characterization result diagram of the slag-based fine aggregate in Comparative Example 2.
[0030] Figure 5 This is the XRD test result diagram of the slag-based cementitious material in Example 2 and Comparative Example 3.
[0031] Figure 6 The flowchart of the preparation method in Example 1, Example 2 and Example 3. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0034] A slag-based fine aggregate is prepared by raw materials comprising the following components in parts by mass: 100 parts of slag, 0.5-1 parts of nano-alumina and 0.1-0.3 parts of carbon dioxide.
[0035] Optionally, the particle size of the nano-alumina is 10-100 nm.
[0036] The above-mentioned method for preparing slag-based fine aggregate comprises the following steps:
[0037] S11, crushing the slag into a set particle size;
[0038] S12, carbonizing the crushed slag for 2-4 hours under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5 MPa;
[0039] S13, mixing and stirring the carbonized slag with nano-alumina to obtain slag-based fine aggregate.
[0040] Optionally, in S11, the slag is crushed to a particle size of 0.1-5 mm.
[0041] Optionally, in S11, the crushed slag is cleaned and then air-dried until the surface is dry.
[0042] Optionally, in S12, 0.1~0.3 parts of carbon dioxide are added in the form of a mixed gas with a set concentration and gas pressure difference, and the amount of carbon dioxide added is not less than the carbonization reaction amount of the crushed slag; carbonization is carried out in an environment with a humidity of 40%~70% and a temperature of 30~40°C, and the water required for the carbonization process is provided by a humid environment.
[0043] Optionally, in S13, after the nano-alumina is mixed with the slag fine aggregate, the nano-material is filled into the micro-cracks of the slag particles by mechanical stirring; wherein the nano-alumina is filled with gas at a pressure of 0.1-0.5 MPa at a speed of 5-10 m / s in the mixer to perform airflow-assisted filling, so that the nano-alumina can better penetrate into the micro-cracks of the slag-based fine aggregate.
[0044] Optionally, in S12, after carbonization is completed, cooling to room temperature is performed in a dry and ventilated environment.
[0045] Optionally, in S13, the stirring speed is 60-80 r / min, and the stirring time is 30-40 min.
[0046] A slag-based ultra-high performance concrete comprises the following components in parts by weight: 550-650 parts of cement, 145-175 parts of fly ash, 124-146 parts of silica fume, 200-300 parts of the above-mentioned slag-based cementitious material, 400-500 parts of the above-mentioned slag-based fine aggregate, 400-500 parts of natural river sand, 60-100 parts of fiber, 4-8 parts of water reducer and 190-250 parts of water; the slag of the above-mentioned slag-based cementitious material and the slag of the above-mentioned slag-based fine aggregate have the same source; the raw materials for preparing the slag-based cementitious material include: slag and carbon dioxide in a mass ratio of 100:(0.1-0.3).
[0047] Optionally, the cement, fly ash and silica fume meet the technical specifications for the preparation and application of ultra-high performance concrete as required by natural river sand.
[0048] Optionally, the fiber is a steel fiber with a length of 13 mm and a width of 0.2 mm.
[0049] Optionally, the water reducing agent is a polycarboxylic acid-based high-performance water reducing agent with a water reduction rate of more than 30%.
[0050] The method for preparing the above-mentioned slag-based ultra-high performance concrete comprises the following steps:
[0051] S31, mixing cement, fly ash, silica fume, slag-based cementitious material, slag-based fine aggregate and natural river sand to obtain a mixed material;
[0052] S32, mixing water and a water reducing agent, adding the mixture to the mixed material and stirring to obtain an ultra-high performance concrete slurry;
[0053] S33, adding fibers to the ultra-high performance concrete slurry, stirring and pouring into shape;
[0054] S34. The poured ultra-high performance concrete is subjected to carbon dioxide curing under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5 MPa for 24-48 hours.
[0055] Optionally, in S31, the stirring time is 1 to 2 minutes; in S32, the stirring time is 3 to 5 minutes; in S33, the stirring time is 2 to 3 minutes.
[0056] Optionally, in S34, carbon dioxide curing is carried out after demoulding 1 day after pouring, and then standard curing is continued for 7 to 14 days.
[0057] In the above-mentioned method for preparing the slag-based ultra-high performance concrete, the method for preparing the slag-based cementitious material comprises the following steps:
[0058] S21, grinding the slag to a set particle size;
[0059] S22, calcining the ground slag at 1150-1250° C. for 2-2.5 h to obtain slag clinker;
[0060] S23. Carbonize the calcined slag clinker for 2 to 4 hours under the conditions of a carbon dioxide concentration of 20 to 30% and a gas pressure difference of 0.4 to 0.5 MPa to obtain a slag-based cementitious material.
[0061] Optionally, in S21, the slag is crushed and then ground to a particle size of 1 to 75 μm;
[0062] Optionally, in S23, the carbonization temperature is 30-40°C;
[0063] Optionally, in S23, after carbonization is completed, cool to room temperature in a dry and ventilated environment.
[0064] The application of the above-mentioned slag-based ultra-high performance concrete is to use the slag-based ultra-high performance concrete in the fields of bridge engineering and underground engineering.
[0065] The tunnel slag in the following embodiments and comparative examples comes from the waste slag excavated during urban tunnel construction, and its main chemical components are silicon dioxide and aluminum oxide, which are similar to the chemical composition of fine aggregate commonly used in ultra-high performance concrete.
[0066] Example 1
[0067] A slag-based fine aggregate, the preparation method of which is as follows Figure 6 As shown, including:
[0068] S11. Wash the slag with clean water to remove surface impurities and dry it. Use a jaw crusher to crush the slag to a particle size of less than 5 mm, and sieve out particles with a particle size of 1 to 5 mm to meet the particle size requirements of ultra-high performance concrete fine aggregate.
[0069] S12. Place the slag-based fine particles in a closed reaction chamber filled with industrial carbon dioxide gas for carbonization reaction. The gas in the closed reaction chamber is prepared by carbon dioxide gas with a purity greater than 99%, the volume concentration of carbon dioxide is 25% (the remaining gas is air), the gas pressure difference in the closed reaction chamber and the pressure difference outside the closed reaction chamber are 0.5MPa, the temperature is 35±2℃, and the carbonization reaction time is 4h. After the carbonization is completed, take the material out of the reaction chamber and place it in a dry and ventilated environment to cool to room temperature.
[0070] S13, adding the carbonized slag-based fine particles into a mixer, adding 1wt% of nano-alumina with a particle size of 70nm in proportion, and dry-mixing at a stirring speed of 60 r / min for 40 minutes to obtain Figure 1 The slag-based fine aggregate shown in the figure; wherein the gas with a pressure of 0.5MPa is filled into the mixer at a speed of 5m / s to perform airflow-assisted filling of the nano-alumina, so that the nano-alumina can better penetrate into the micro-cracks of the slag-based fine aggregate.
[0071] Due to the tunnel construction process, there are a large number of microcracks and structural defects inside the tunnel slag; the calcium carbonate component is generated through the carbonization process of S12, which first fills the larger cracks and pores, while the nano-alumina used in S13 can play a mechanical filling role in finer cracks, including fine cracks on the surface of fine aggregates and small cracks remaining from large cracks after the carbonization process, providing a higher level of repair effect and forming a dual repair mechanism. The microscopic characterization results are shown in Figure 2. Figure 2 As shown, it indicates that the microcracks and pores in the slag can be effectively repaired to reduce the water absorption and expansion. The water absorption is measured to be 2%~4%, and the expansion property is non-expansion or the expansion rate is reduced by 50% compared with the slag without any treatment.
[0072] Comparative Example 1
[0073] A slag-based fine aggregate, which is different from the preparation method of Example 1 in that only steps S11 and S12 are used, and step S13 is not used.
[0074] The microscopic characterization results are as follows Figure 3 As shown, it can be seen that at the same magnification as in Example 1, microcracks still exist after only carbonization with carbon dioxide, indicating that the repair of small cracks is limited.
[0075] Comparative Example 2
[0076] A slag-based fine aggregate, which is different from the preparation method of Example 1 in that only steps S11 and S13 are used, and step S12 is not used.
[0077] The microscopic characterization results are as follows Figure 4 As shown, it can be seen that at the same magnification as in Example 1, larger cracks still exist after only nano-repair, indicating that the repair of larger cracks is limited.
[0078] Example 2
[0079] A slag-based cementitious material, the preparation method of which is as follows Figure 6 As shown, including:
[0080] S21. Wash the slag with clean water to remove surface impurities and dry it. Use a ball mill to crush and grind the slag to a particle size of less than 75μm, and sieve out powder with a particle size of 1~75μm.
[0081] S22, calcining the sieved powder at 1200°C for 2.5 hours, and then cooling it at room temperature to obtain slag-based cementitious material clinker.
[0082] S23. Place the slag-based cementitious material clinker in a closed reaction chamber filled with industrial carbon dioxide gas for carbonization reaction. The gas in the closed reaction chamber is prepared by carbon dioxide gas with a purity greater than 99%, and the volume concentration of carbon dioxide is 25%. The gas pressure difference in the closed reaction chamber is 0.5MPa, the temperature is 35±2℃, and the carbonization reaction time is 4h. After the carbonization is completed, take the material out of the reaction chamber, place it in a dry and ventilated environment, and cool it to room temperature to obtain the slag-based cementitious material.
[0083] The obtained slag-based cementitious material was subjected to XRD test. The results are as follows: Figure 5 As shown, it is shown that its main components are quartz and albite.
[0084] Example 3
[0085] A slag-based ultra-high performance concrete comprises the following components in parts by weight: 560 parts of cement, 160 parts of fly ash, 132 parts of silica fume, 240 parts of the slag-based cementitious material in Example 2, 450 parts of the slag-based fine aggregate in Example 1, 450 parts of natural river sand, 78.5 parts of fiber, 6 parts of water reducer and 210 parts of water.
[0086] Among them, cement, fly ash, silica fume and natural river sand meet the technical specifications for the preparation and application of ultra-high performance concrete, specifically: cement is ordinary Portland cement of grade 52.5 or 52.5R; fly ash is grade I, with a loss on ignition less than 3.0% and a specific surface area greater than 1000cm2 / g; the mass percentage of silicon dioxide in silica ash is not less than 97%, the volcanic ash activity index is greater than 95%, the specific surface area is greater than 21.0m2 / g, and the density is 2.20g / cm3; natural river sand has a particle size of less than 5mm and a bulk density of less than 1200kg / m3.
[0087] The fiber is a steel fiber with a length of 13 mm and a width of 0.2 mm and a tensile strength of 2500 MPa.
[0088] The water reducing agent is a polycarboxylic acid-based high-performance water reducing agent with a solid content greater than 20%, a pH value of about 7.5, and a water reduction rate of more than 30%.
[0089] Preparation method Figure 6 As shown, the following steps are included:
[0090] S31. Add cement, fly ash, silica fume, slag-based cementitious materials, slag-based fine aggregate and natural river sand into a mixer, mix and stir for 2 minutes until uniform, and obtain a mixed material.
[0091] S32. Mix water and water reducing agent and add into a mixer, and stir rapidly for 5 minutes to obtain ultra-high performance concrete slurry.
[0092] S33. During the continuous stirring process, steel fibers are sprinkled into the mixer to prevent agglomeration. The stirring is continued for 3 minutes to obtain the slag-based ultra-high performance concrete slurry, which is then poured into shape.
[0093] S34. After 1 day of pouring, the ultra-high performance concrete is demolded and transferred to a standard curing room. A carbon dioxide gas with a volume concentration of 30% (prepared with carbon dioxide with a concentration greater than 99%) is injected into the curing room. The gas pressure in the curing room is 0.5MPa greater than that outside the curing room. After 48 hours of curing, the carbon dioxide gas is gradually released and the concrete is cured in the standard curing room for 10 days to obtain slag-based ultra-high performance concrete.
[0094] Comparative Example 3
[0095] An ultra-high performance concrete containing slag-based fine aggregate comprises the following components in parts by weight: 800 parts of cement, 160 parts of fly ash, 132 parts of silica fume, 450 parts of the slag-based fine aggregate in Example 1, 450 parts of natural river sand, 78.5 parts of fiber, 6 parts of water reducer and 210 parts of water.
[0096] The preparation and curing methods are the same as those in Example 3, and the difference from Example 3 is that the slag-based cementitious material in Example 3 is replaced by cement with the same mass fraction.
[0097] Comparative Example 4
[0098] An ultra-high performance concrete containing slag-based fine aggregate comprises the following components in parts by weight: 560 parts of cement, 160 parts of fly ash, 132 parts of silica fume, the slag-based cementitious material that has only undergone step S21 in Example 2, 450 parts of the slag-based fine aggregate in Example 1, 450 parts of natural river sand, 78.5 parts of fiber, 6 parts of water reducer and 210 parts of water.
[0099] The preparation and curing methods are the same as those in Example 3, and the difference from Example 3 is that the slag-based cementitious material in Example 3 is replaced by the slag-based cementitious material of Example 2 that has only undergone step S21 with the same mass fraction.
[0100] Comparative Example 5
[0101] An ultra-high performance concrete containing slag-based cementitious material comprises the following components in parts by weight: 560 parts of cement, 160 parts of fly ash, 132 parts of silica fume, 240 parts of the slag-based cementitious material in Example 1, 900 parts of natural river sand, 78.5 parts of fiber, 6 parts of water reducer, and 210 parts of water.
[0102] The preparation and curing methods are the same as those in Example 3, and the difference from Example 3 is that the slag-based fine aggregate in Example 3 is replaced by natural river sand of the same mass fraction.
[0103] Comparative Example 6
[0104] An ultra-high performance concrete comprises the following components in parts by weight: 800 parts of cement, 160 parts of fly ash, 132 parts of silica fume, 900 parts of natural river sand, 78.5 parts of fiber, 6 parts of water reducing agent and 210 parts of water.
[0105] The preparation and curing methods are the same as those in Example 3, and the difference from Example 3 is that the slag-based cementitious material in Example 3 is replaced by cement of the same mass fraction, and the slag-based fine aggregate is replaced by natural river sand of the same mass fraction.
[0106] Comparative Example 7
[0107] A slag-based ultra-high performance concrete using slag-based cementitious materials and slag-based fine aggregate, the preparation raw materials of which are the same as those in Example 3.
[0108] The preparation method includes steps S31, S32, and S33 in Example 3, and the difference from Example 3 is that in step S34, the mold is removed after 1 day and the mixture is transferred to a standard curing room for curing for 12 days, that is, carbon dioxide curing is not used.
[0109] Test Case
[0110] The total crack area per unit area was obtained by adding up the surface crack areas of the specimens after curing in Example 3 and Comparative Examples 2, 3, 4, and 5, and dividing the total crack area by the total surface area of the specimens. The results are shown in Table 1.
[0111] The materials obtained from Example 3 and Comparative Examples 2, 3, 4, and 5 were tested, including expansion, compressive strength, 7d shrinkage, electric flux, and impermeability grade. The results are shown in Table 1.
[0112] The test results are shown in Table 1.
[0113] Table 1 Ultra-high performance concrete performance test results
[0114]
[0115] As can be seen from Table 1, the ultra-high performance concrete in Example 3 and the comparative example showed significant differences in multiple performance indicators, especially in compressive strength and crack control. The compressive strength of Example 3 reached 85.4 MPa, 104.8 MPa and 132.6 MPa at 3 days, 7 days and 28 days, respectively, which were higher than those of Comparative Examples 3 to 6. In addition, at 3 days and 28 days, the difference between Example 3 and Comparative Example 6 was higher than the sum of the differences between Comparative Example 4 and Comparative Example 5 and Comparative Example 6, indicating that there was a synergistic effect between the slag-based cementitious material and the slag-based fine aggregate, and the improvement effect of the comprehensive addition was due to the sum of the improvement effects of the two added separately. After the slag was subjected to multiple treatments, the slag-based cementitious material increased its activity, and the slag-based fine aggregate repaired microcracks, which comprehensively improved the strength and density of the concrete, thereby effectively improving the mechanical properties of the concrete. At the same time, the early strength of concrete was significantly enhanced under the condition of carbon dioxide curing. The 3d and 7d strengths of Example 3 increased by 23% compared with those of Comparative Example 7. In addition, the total cracking area per unit area of Example 3 was 116.7 mm² / m², and the shrinkage rate was 578µm, which was significantly lower than that of Comparative Examples 3 to 7, indicating that the slag-based concrete has better performance in reducing crack generation and early self-shrinkage. This is mainly due to two reasons. The slag-based cementitious material replaced part of the cement, reduced the hydration heat, and controlled the cracking of UHPC caused by self-shrinkage and thermal stress; the slag-based fine aggregate, due to its irregular surface shape, enhanced the mechanical bite force between the concrete matrix and the aggregate, and improved the ability of the fine aggregate to restrain the shrinkage of the cement slurry. At the same time, after being treated with nano-repair materials and carbon dioxide, the volume stability of the material was also guaranteed.
[0116] In terms of chloride ion corrosion resistance, the electric flux of Example 3 is only 21C, which is significantly lower than that of Comparative Examples 3 to 7, meeting the performance requirements of ultra-high performance concrete and showing better impermeability. This shows that the addition of treated slag material makes the internal structure of concrete more compact and the porosity is reduced, thereby significantly improving the impermeability.
[0117] In addition, the water-resistance grades of Comparative Examples 3, 5 and 6 are all >10, indicating that adding slag-based fine aggregate or slag-based fine aggregate alone cannot effectively improve their water-resistance grades, while the water-resistance grade of Example 3 is >12, further indicating that adding slag-based fine aggregate and slag-based fine aggregate at the same time has a synergistic effect, reflecting the advantages of the present invention in terms of waterproofness and durability.
[0118] The chemical composition of slag-based fine aggregate and slag-based cementitious materials is similar, which means that the two have better compatibility in concrete. Since they are derived from slag, the interfacial bonding force between them is high, and the fine aggregate can better combine with the cementitious material to form a dense interfacial transition zone (ITZ). The density of the interfacial transition zone is crucial to the overall mechanical properties, crack resistance, and durability of UHPC.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A slag-based fine aggregate, characterized in that: The raw materials include the following components by weight: 100 parts of slag, 0.5-1 parts of nano-alumina and 0.1-0.3 parts of carbon dioxide; The method for preparing slag-based fine aggregate comprises the following steps: S11, crushing the slag into a set particle size; S12, carbonizing the crushed slag for 2-4 hours under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5Mpa; S13, mixing and stirring the carbonized slag with nano-alumina to obtain slag-based fine aggregate; In S11, the slag is crushed to a particle size of 0.1-5 mm; In S12, carbonization is performed in an environment with a humidity of 40% to 70% and a temperature of 30 to 40°C; In S13, gas with a pressure of 0.1-0.5 MPa is charged at a speed of 5-10 m / s to perform airflow-assisted filling of the nano-alumina.
2. The slag-based fine aggregate according to claim 1, characterized in that: The particle size of nano-alumina is 10~100nm.
3. A method for preparing slag-based fine aggregate according to any one of claims 1 to 2, characterized in that: The following steps are involved: S11, crushing the slag into a set particle size; S12, carbonizing the crushed slag for 2-4 hours under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5Mpa; S13, mixing and stirring the carbonized slag with nano-alumina to obtain slag-based fine aggregate.
4. The method for preparing slag-based fine aggregate according to claim 3, characterized in that: In S12, carbonization is performed in an environment with a humidity of 40% to 70% and a temperature of 30 to 40°C.
5. A slag-based ultra-high performance concrete, characterized in that: The invention comprises the following components in parts by weight: 550-650 parts of cement, 145-175 parts of fly ash, 124-146 parts of silica fume, 200-300 parts of slag-based cementitious material, 400-500 parts of slag-based fine aggregate as claimed in any one of claims 1-2, 400-500 parts of natural river sand, 60-100 parts of fiber, 4-8 parts of water reducer and 190-250 parts of water; The slag of the slag-based cementitious material and the slag of the slag-based fine aggregate have the same source; The raw materials for preparing the slag-based cementitious material include: slag and carbon dioxide in a mass ratio of 100:(0.1-0.3); The method for preparing the slag-based cementitious material comprises the following steps: S21, grinding the slag to a set particle size; S22, calcining the ground slag at 1150-1250° C. for 2-2.5 h to obtain slag clinker; S23, carbonizing the calcined slag clinker for 2 to 4 hours under the conditions of a carbon dioxide concentration of 20 to 30% and a gas pressure difference of 0.4 to 0.5 MPa to obtain a slag-based cementitious material; In S21, the slag is crushed and ground to a particle size of 1 to 75 μm.
6. A method for preparing slag-based ultra-high performance concrete according to claim 5, characterized in that: The following steps are involved: S31, mixing cement, fly ash, silica fume, slag-based cementitious material, slag-based fine aggregate and natural river sand to obtain a mixed material; S32, mixing water and a water reducing agent, adding the mixture to the mixed material and stirring to obtain an ultra-high performance concrete slurry; S33, adding fibers to the ultra-high performance concrete slurry, stirring and pouring into shape; S34. The poured ultra-high performance concrete is subjected to carbon dioxide curing under the conditions of a carbon dioxide concentration of 20-30% and a gas pressure difference of 0.4-0.5 MPa for 24-48 hours.
7. The slag-based ultra-high performance concrete according to claim 5, characterized in that: In S23, the carbonization temperature is 30-40°C; In S23, after carbonization is completed, the carbonized product is cooled to room temperature in a dry and ventilated environment.
8. An application of the slag-based ultra-high performance concrete as claimed in claim 5, characterized in that: The application is to use the slag-based ultra-high performance concrete in the fields of bridge engineering and underground engineering.
Citation Information
Patent Citations
All-component carbon dioxide absorption low-carbon concrete composition design method
CN117789876A
Nano-modified internal-curing high-terrestrial heat-resistant full-hole slag concrete and preparation method thereof
CN118495910A